Enabling Human Rights with Universal Acceptance: The Path to the Implementation of Internationalized Domain Names (IDN) and Email Addresses Internationalization (EAI) - Morais, Sávyo V.; Datysgeld, Mark W. (Anais do Workshop Pré-IETF (WPIETF), 2021)
This paper seeks to understand the interactions between Human Rights and the technical aspects of linguistic representation in email systems and the DNS. Based on studies carried out concerning Universal Acceptance and the usage of non-ASCII characters on the Internet, it is proposed that this subject is of relevance to the IETF and the broader technical community that surrounds it. Going over results from recent research on the subject, a case is presented that while there have been advances in the representation of different scripts online, more can be done to ensure that every person is able to experience the network using their native language.